Desarrollo y evaluación de tocino vegano con adición de hongos ostra. - Fierro Valencia, Emily Abigail (2026)
The growing demand for plant-based food products has spurred the development of vegan alternatives that seek to replicate the sensory characteristics of traditional animal-based foods. This project aimed to develop a plant-based bacon substitute with the addition of oyster mushrooms, with the purpose of replicating the sensory characteristics of traditional bacon. The study was conducted using an experimental approach, employing a mixture design to establish the base formulation, which contained plant proteins, corn flour, cassava starch, coconut oil, gelling agents, and stabilizers, to which two variants of oyster mushroom were subsequently added: A (Pleurotus ostreatus) and B (Pleurotus eryngii). A paired-preference sensory analysis was conducted with forty untrained panelists to figure out the best formulation. Subsequently, physicochemical, and microbiological analyzing tests, as well as stability tests, were conducted over 30 days of cold storage under vacuum packaging to ensure the product’s quality and safety. The data indicated that formulation B was preferred by the evaluators. From a nutritional standpoint, the selected product had a protein content of 13,68%, fat 5,78%, moisture 56,40%, ash 2,80%, total carbohydrates 21,34%, calories 192,10 kcal/100 g, and crude fiber 0,78%. It is concluded that the production of a plant-based bacon substitute with the addition of oyster mushrooms is feasible, meeting quality, stability, and consumer preference criteria. This development contributes to the growth of the vegan and plant-based product sector, driving productive diversification in the agro-industry.